Indirect capabilities and complex performance: Implications for procurement and operations strategy. Issue 2 (2014) - ,; ,
Abstract : Purpose – The paper argues that indirect capabilities – the ability to access other organizations' capabilities – are an important and neglected part of firm strategy in procuring complex performance (PCP) settings, and that this is especially so if these settings are treated as genuinely complex, rather than merely complicated. Elements of indirect capabilities are identified. The paper aims to discuss these issues.Design/methodology/approach – This is a theoretical paper, drawing on complexity notions and Penrose's analysis of endogenous innovation to drive a disequilibrium‐oriented discussion of the capabilities required by firms in a PCP setting.Findings – Six inter‐related elements of indirect capabilities are proposed and discussed: IT infrastructure, boundary management practices, contracting, interface artefacts, valuing others' capabilities and relating direct to indirect capabilities. These are important in PCP settings and in other operations and supply settings characterised by complexity.Originality/value – This paper reconsiders the way complexity has been treated in the PCP literature and develops an extended discussion of the notion of indirect capabilities. It potentially provides the basis for an operations and supply strategy more attuned to the demands of shifting inter‐organizational networks.